Can positron emission tomography - computed tomography imaging predict of metastases in patients with small cell lung cancer - Xuan, Ngo Minh; Huy, Huynh Quang (International Journal of Research in Medical Sciences, 2020)
Background: Small-cell lung cancer (SCLC) accounts for 15%-20% of all lung cancer cases. positron emission tomography - computed tomography (PET/CT) has become increasingly used as an initial staging tool in patients with SCLC. We aimed to explore the relationships between primary tumor 18F-FDG uptake measured as the maximum standardized uptake value (SUV max) and clinical stage at PET/CT for small cell lung cancer patients (SCLC). Methods: Patients with SCLC who underwent 18F-FDG PET/CT scans before the treatment were included in the study at Bach Mai hospital of Vietnam, from November 2014 to May 2018. The primary tumor and secondary lesion SUVmax was calculated; the tumor size was measured; the TNM status was determined mainly by FDG PET/CT imaging according to The 8th Edition of the TNM Classification for Lung Cancer were recorded. An evaluation was made of the linear relationship between tumor size, T stage, N stage, and M stages of the patients and their SUVmax using Spearman’s correlation. Results: Total 37 cases (34 men and 3 women; age range 38 - 81 years, median 64 years) were analyzed. The average of primary tumor size and SUVmax were 5.95±2.77 cm and 10.21±4.75, respectively. The SUVmax of primary tumor is significantly greater than that of nodal and distant organ metastasis (10.21±4.75 vs 8.20±4.35 and 6.44±3.17, p<0.01). There was a moderate correlation between SUVmax and tumor size (r =0.596, p<0.001), tumor stage (r = 0.502, p<0.01) but not significant with nodal stage (r =-0.218, p=0.194), metastasis stage (r = -0.055, p=0.747), and overall stage (r=-0.060, p=0.725). Conclusions: SUVmax was significantly correlated with tumor size, but not with distant metastases or lymph node involvement. Therefore, SUVmax on positron emission tomography is not predictive of the presence of metastases in patients with SCLC.